Lassa Virus Nucleoprotein Mutants Generated by Reverse Genetics Induce a Robust Type I Interferon Response in Human Dendritic Cells and Macrophages - Carnec, Xavier (American Society for Microbiology, 2011)
Lassa virus (LASV; Arenaviridae) is responsible for severe hemorrhagic fevers in Africa. LASV nucleoprotein (NP) plays important roles in regulating viral transcription and replication and in inhibiting type I interferon (IFN) production. The NP C-terminal domain contains a 3′-to-5′ exonuclease activity involved in suppressing IFN induction. We have established a murine polymerase (Pol) I reverse genetics system for LASV, showing that residues D389 and G392 of NP were critical for LASV viability, while the D389A/G392A and D389T/392A double mutants were severely altered in the ability to suppress IFN in macrophages and dendritic cells. Assessing their attenuation in vivo may open new perspectives in vaccinology.